Evasão escolar na comunidade remanescente de Quilombo de Rincão dos Caixões (Jacuizinho – RS): uma análise interseccional dos fatores causais e possíveis estratégias de enfrentamento - Rocha, Gisele da (2023)
Why do the majority of students from the Quilombo Remaining Community of Rincão dos Caixões (Jacuizinho – RS) not complete Basic Education? Aiming to study this problem as well as to identify possible coping actions, this research is developed. The research methodology is initially quantitative, with the State of the Art (BARROS, 2011), followed by the qualitative approach (ANDRÉ and GATTI, 2013), with data production through bibliographical research (GIL, 2002) and field research ( MARKONI and LAKATOS (1996) instrumented by questionnaires (GIL, 1999), (auto)biographical narratives (ABRAHÃO, 2003) and action research (DIONNE, 2007), with an intersectional analysis of the data (FELTRIN et al, 2021). Revisit the black history regarding the fight for the right to education (FONSECA, 2001; DOMINGUES, 2007) complemented by a brief examination of the relevance of education for ethnic-racial relations (GOMES, 2001), under the assumption that a student's identity construction is tied to the respect and appreciation of their particularities, including ethnicity/race. Learning, in turn, is connected to identity construction (MUNANGA, 1999; SILVA, 2018). In this context, the research discusses some aspects of the local reality (NOGUEIRA, 2005), pedagogical work related to quilombola students, and actions taken by the government in response to dropout rates, including teacher training (PINTO, 2018), culminating in an effort to redevelop the Pedagogical Political Project of each municipal school. The study of the quilombola community highlights that encouragement for education has been present since the matriarch's arrival in the municipality (ANJOS, 2009), as confirmed by the narratives of students, former students, and their families collected during visits to the community, as well as during the last stage of this study: a roundtable discussion with all quilombola students from the 5th grade of Elementary School to the 3rd year of High School (RIBEIRO, 2019). All the data collected, subjected to an intersectional analysis, result in recommendations regarding the urgency of actions aimed at mitigating dropout rates, primarily driven by early pregnancy and marriage, entry into the workforce, and a lack of motivation for further studies. The visibility of this important debate, for which academic research is limited, and the collaboration of individuals committed to social change (FREIRE, 1982) are essential components in fostering reflection on school dropout among quilombola students, even within Basic Education.